The genome sequence of a tachinid fly, Linnaemya vulpina (Fallén, 1810) [version 1; peer review: 2 approved] - Olga Sivell; Chris Raper; Ryan Mitchell (Wellcome Open Research, 2024)
We present a genome assembly from an individual male tachinid fly, Linnaemya vulpina (Arthropoda; Insecta; Diptera; Tachinidae). The genome sequence has a total length of 554.00 megabases. Most of the assembly (98.85%) is scaffolded into 7 chromosomal pseudomolecules, including the X and Y sex chromosomes. The mitochondrial genome has also been assembled and is 16.72 kilobases in length. Gene annotation of this assembly on Ensembl identified 11,599 protein-coding genes.